The Role of Social Media Influencers in Influencing Consumption Patterns: Microeconomic and Market Change Perspectives - Rokhadi (PT. LITERASI SAINS NUSANTARA, 2023)
Social media users not only consume content but also become part of the marketing process by becoming followers of influencers. From a microeconomic perspective, the role of social media influencers can be understood as a factor influencing product demand and supply. Their influence on consumer preferences can change market dynamics and company marketing strategies. The aim of this research is to investigate more deeply how the role of social media influencers affects consumption patterns from a microeconomic perspective, focusing on changes occurring in the market. The research method employed is a literature review with a qualitative approach using descriptive analysis. Data for this research are collected from Google Scholar, spanning from the years 2016 to 2023. The study findings indicate that in the current digital era, the role of social media influencers has significantly transformed societal consumption patterns. In this microeconomic analysis, we observe how influencers influence consumer behavior through shifts in demand curves, creation of emotional associations between products and consumers, acceleration of trend cycles, and product differentiation. Despite having positive impacts such as increased demand elasticity and product differentiation, the role of influencers also poses risks related to authenticity, transparency, and the adoption of irrational consumer behavior.